Dark rose: organized crime and corruption in Portland - Donnelly, Robert C. (University of Washington Press)
Early Portland and the failure of progressive reform -- Post-World War II Portland -- Elkins vs. the Teamsters -- The Portland vice scandal -- The McClellan Committee